MOTIVASI ORANG TUA DALAM PENENTUAN PENDIDIKAN TINGGI ANAK DI KELURAHAN MERI KOTA MOJOKERTO - Anis Fitri Alviana; Raden Roro Nanik Setyowati (Kajian Moral dan Kewarganegaraan, 2023)
The purpose of this research is to describe the motivation of parents in determining their children's higher education in Meri Village, Mojokerto City. The focus of this study is the analysis of parents' motivation in making decisions regarding their children's further higher education. The theoretical foundation used is Abraham Maslow's motivational theory consisting of several indicators, namely physiological needs, safety needs, social needs, esteem needs, and self-actualization needs. This study used qualitative research with a descriptive research design. The informants of this study were three parents who had teenagers aged 18 to 19 years who continued their education at tertiary institutions. Data collection techniques in this study were in-depth interviews and observation. The data validation technique uses technical triangulation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of research on parents' motivation in determining their children's tertiary education so that children can get a better education, get decent jobs in the future, gain existence in the family and community environment, get support and assistance from extended families, and can form good character and morals. better. It's just that in the process of discussing the determination of further higher education, there are differences of opinion between parents and children when they have different choices of majors. The child agrees to follow directions and the parents enter the department according to the wishes of the parents because they feel that the parents' choice is not bad and is a form of child's devotion to their parents. Keywords: motivation, parents, child’s higher education